Admission lactate level and the GRACE 2.0 score are independent and additive predictors of 30-day mortality of STEMI patients treated with primary PCI - preliminary results of a real-world registry. (26th April 2021) - Szabo, D; Szabo, A; Kugler, S; Pinter, A; Juhasz, V; Ruppert, M; Olah, A; Edes, IF; Becker, D; Merkely, B; Hizoh, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background In many of the current risk estimation algorithms for patients with ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI), heart rate and systolic blood pressure are key predictors. Yet, these parameters may also be influenced by the actual medical treatment / circulatory support, thereby decreasing the discriminatory power of the models.  Purpose   We aimed to investigate whether venous lactate level, a marker of microcirculatory failure, may have an added prognostic value beyond conventional predictors. Methods In a pilot real-world registry, 174 cases were studied. Venous blood gas analysis was performed in all patients at hospital admission. Nested logistic regression models were built using the extensively validated "Global Registry of Acute Coronary Events" (GRACE) 2.0 score alone (base model) or with the addition of venous lactate level (expanded model) using 30-day all-cause mortality as outcome measure. Independence of predictors (lack of collinearity) was evaluated  by the variance inflation factor (VIF). Instead of the insensitive c-statistic, difference in performance of the nested models was analyzed by the likelihood ratio test and the integrated discrimination improvement (IDI). Results The VIF was 1.0684, indicating independence of the measured lactate values from  the calculated GRACE 2.0 scores. Both base and expanded models showed high discriminatory power: c-statistic = 0.88 and 0.89, respectively, p = 0.68). Nevertheless, addition of venous lactate level to the GRACE 2.0 score improved predictions of 30-day mortality significantly as assessed by  both likelihood ratio test (chi-square = 8.97, p = 0.0027) and IDI (IDI = 0.1029, 95% CI: 0.0002-0.2055, p = 0.0494).  Conclusions Venous lactate level may be an independent predictor of 30-day mortality of STEMI patients treated with primary PCI. The addition of this marker to the GRACE 2.0 model may improve mortality prediction of these patients.